Defining digital-Foley for live performance. (22nd December 2014) - Challis, Ben; Dean, Rob
Using a series of reflective case-studies, the role of the Foley artist is reconsidered alongside technological innovations in both digital sound manipulation and physical computing. Through a series of theatrical productions and collaborations Challis and Dean have explored the sonic and dramatic possibilities created by the utilisation of digital technology in a live performance context. In this article, a variety of approaches to electronic sound-production and control are described along with first-hand reflections on the expressivity and control that are offered by each within a context of live drama. Their current project is a multimedia adaptation of the novel and film Metropolis where the aural accompaniment will be performed live using a range of adapted and purpose built sonic triggers. In defining digital-Foley, design considerations and key principles are outlined that can enhance the connectivity between the sound-artist and the sonic-landscapes they create.